Evanescent wave broadband cavity enhanced absorption spectroscopy using supercontinuum radiation: A new probe of electrochemical processes - Schnippering, M; Unwin, P; Hult, J; Laurila, T; Kaminski, C; Langridge, J; Jones, R; Mazurenka, M; Mackenzie, S (Elsevier, 2008)
An evanescent wave variant of broadband cavity enhanced absorption spectroscopy using a supercontinuum light source has been used to detect electrogenerated species at the silica-water interface. In proof-of-concept experiments [IrCl6]2− was produced by electro-oxidation of [IrCl6]3− in a thin layer electrochemical cell. Diffusion of the Ir(IV) across the cell to a silica interface was monitored yielding real-time concentrations within an evanescent field region at the interface. The optical response was compared with the electrochemical response during chronoamperometric step and cyclic voltammetric experiments and both were simulated by finite element modeling. The experiment is highly sensitive to interfacial processes and its wide spectral width and fast time resolution make it a potentially powerful tool for in situ spectroscopic monitoring of processes and intermediates in dynamical electrochemistry.